Specifics of business trips (official journeys) under Czech legislation (Discourse of Law and Administration, 2022)
In the submitted article, the authors deal with the Czech legal regulation of business trips (official journeys). The authors focus on the legal regulation of business trips of employees whose employment relationships are governed by the Czech Labour Code, as well as on official journeys of persons in a civil service employment, such as civil servants, members of the security forces and professional soldiers. In the article, in addition to the conditions under which these persons may be instructed to go on a business trip, the authors also examine the xtent to which the protective function of labour law affects various categories of persons.
Keywords: Business trip; employment; protective function of labour law; autonomy of will; public service employment